A Comparison of the Effects of Aerobic and Intense Exercise on the Type 2 Diabetes Mellitus Risk Marker Adipokines, Adiponectin and Retinol Binding Protein-4. (12th January 2014) - Phillips, Amy; Cobbold, Christian
Abstract : With a more sedentary population comes growing rates of obesity and increased type 2 diabetes mellitus (T2DM) risk. Exercise generally induces positive changes in traditional T2DM risk markers such as lipids, glucose tolerance, and insulin sensitivity; however alterations in concentrations of many circulating cytokines and their respective receptors are also becoming apparent. These cytokines may be early-response health risk factors otherwise overlooked in traditional T2DM risk marker analysis. Plasma levels of two adipocyte-originating cytokines, adiponectin and retinol binding protein 4 (RBP-4), alter following exercise. Adiponectin has anti-inflammatory, anti-atherosclerotic, and anti-insulin resistance roles and its secretion increases with physical activity, whilst elevated RBP-4 leads to increased insulin resistance, and secretion decreases with increasing physical activity; thus these plasma adipokine levels alter favourably following exercise. Although current data are limited, they do suggest that the more intense the exercise, the greater the positive effect on plasma RBP-4 levels, whilst lower intensity aerobic exercise may positively improve adiponectin concentrations. Therefore short-duration, high intensity training may provide a time-efficient alternative to the recommended 150 min moderate aerobic exercise per week in providing positive changes in RBP-4 and other traditional T2DM risk markers and due to increased compliance give greater health benefits over the longer term.